(3GdLhGgQ GdRcjI aj Md CdaGX GdYTeGhjIs - (3CMeO Hf JQcj Hf CMeO GdeGdcjs; (3YHO GdHGQj GdYTeGhj GdQaGYj, CHhGdYHGSs ((3eMeO Hf YHOGddg Hf CHj Hdd s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ GdMbjQ CMeO Hf JQcj Hf CMeO bO GdJeS efj HYV GdENhGf Cf CdNU dge GdTQM GdPj LYdg GdTjN SjOj eMeO Hf eMeO GdajTj Ydi ebOeI GdTjN YHOGdHGQj GdYTeGhj s
(3BNQgG (B:s
(3QHfG CJfG aj GdOfjG MSfI hai GdBNQI MSfI hbfG YPH GdfGQ hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs